Future crop risk estimation due to drought, extreme temperature, hail, lightning, and tornado at the census tract level in Louisiana - Mostafiz, Rubayet Bin; Rohli, Robert V.; Friedland, Carol J.; Gall, Melanie; Bushra, Nazla (Frontiers in Environmental Science, 2022)
Louisiana is one of the most hazard-prone states in the U.S., and many of its people are engaged directly or indirectly in agricultural activities that are impacted by an array of weather hazards. However, most hazard impact research on agriculture to date, for Louisiana and elsewhere, has focused on floods and hurricanes. This research develops a method of future crop loss risk assessment due to droughts, extreme low and high temperatures, hail, lightning, and tornadoes, using Louisiana as a case study. This approach improves future crop risk assessment by incorporating historical crop loss, historical and modeled future hazard intensity, cropland extent, population, consumer demand, cropping intensity, and technological development as predictors of future risk. The majority of crop activities occurred and will continue to occur in south-central and northeastern Louisiana along the river basins. Despite the fact that cropland is decreasing across most of the state, weather impacts to cropland are anticipated to increase substantially by 2050. Drought is by far the costliest among the six hazards, accounting for $56.1 million of $59.2 million (∼95%) in 2050-projected crop loss, followed by extreme cold ($1.4 million), extreme heat ($1.0 million), tornadoes ($0.4 million), hail ($0.2 million), and lightning ($0.05 million), respectively. These findings will assist decision-makers to minimize risk and enhance agricultural resilience to future weather hazards, thereby strengthening this economically-important industry in Louisiana and enhancing food security.